2011
DOI: 10.1007/s10863-011-9342-y
|View full text |Cite
|
Sign up to set email alerts
|

NMR solution structure of subunit E (fragment E1–69) of the Saccharomyces cerevisiae V1VO ATPase

Abstract: The N-terminus of V-ATPase subunit E has been shown to associate with the subunits C, G and H, respectively. To understand the assembly of E with its neighboring subunits as well as its N-terminal structure, the N-terminal region, E(1-69), of the Saccharomyces cerevisiae V-ATPase subunit E was expressed and purified. The solution structure of E(1-69) was determined by NMR spectroscopy. The protein is 90.3 Å in length and forms an á-helix between the residues 12-68. The molecule is amphipathic with hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As shown for the N-and C-terminal domains of the solution NMR structure of the yeast V-ATPase, subunit E forms a bent N-terminal α-helix 36 and a C-terminal globular domain with a secondary structural arrangement of β1:α1:β2:β3:β4:α2, which is connected by flexible loop regions. 37 Although the number of peripheral stalks in V-ATPases is still under debate, 38 the homologous subunits E and G (homologue to H in A-ATP synthases) of the eukaryotic enzyme may fulfill a similar function of storage of transient elastic energy during the coupled processes of ATP hydrolysis and proton pumping.…”
Section: Flexibility Of the Peripheral Stalk For Enzyme Functionmentioning
confidence: 99%
“…As shown for the N-and C-terminal domains of the solution NMR structure of the yeast V-ATPase, subunit E forms a bent N-terminal α-helix 36 and a C-terminal globular domain with a secondary structural arrangement of β1:α1:β2:β3:β4:α2, which is connected by flexible loop regions. 37 Although the number of peripheral stalks in V-ATPases is still under debate, 38 the homologous subunits E and G (homologue to H in A-ATP synthases) of the eukaryotic enzyme may fulfill a similar function of storage of transient elastic energy during the coupled processes of ATP hydrolysis and proton pumping.…”
Section: Flexibility Of the Peripheral Stalk For Enzyme Functionmentioning
confidence: 99%
“…Studies using x-ray crystallography and electron microscopy have predicted that yeast V-ATPase has three peripheral stalks that are supporting the catalytic A 3 B 3 hexamer, with each of them formed from a heterodimer of the E and G subunits (7)(8)(9)(10)(11). NMR spectroscopy of the 69 amino-terminal residues of the yeast E subunit (12), and crystal structure analyses of the heterotrimeric EGC complexes (Protein Data Bank codes 4DL0 and 4EFA) have shown that the yeast V-ATPase E and G subunits have an amino-terminal right-handed coiled-coil structure that allows intrinsic flexibility to the stalks (8). The structural flexibilities of the peripheral stalks would allow conformational transition between catalytic sites in the A 3 B 3 hexamer (13).…”
mentioning
confidence: 99%
“…The E subunits are well conserved, and those of mouse and yeast share ϳ30% amino acid identity. Secondary structure prediction analyses have indicated even higher simi-* This work was supported by grants-in-aid from Japanese Society for the larity in their structures (12,23). We have previously shown that a null mutant of yeast E subunit (⌬vma4) (24) expressing E1 or E2 grows at alkaline pH and that the mouse E1 or E2 yeast hybrid V-ATPase transports protons, indicating that the mouse isoforms are functional in yeast (22).…”
mentioning
confidence: 99%
“…In the last decade, the structures of the individual eukaryotic V-ATPase subunits C (14), E (15)(16)(17), F(1-94) (18), G (15,19,20), and H (21) were determined, all from the Saccharomyces cerevisiae enzyme. These structures fit into a cryo-EM map of the S. cerevisiae V-ATPase as shown in Fig.…”
mentioning
confidence: 99%